Conhece-te a ti mesmo: interculturalidade e resgate de narrativas de culturas populares espontâneas - Dugnani, Patricio (2025)
The aim of this article is to reflect on how the unbalanced relationship between spontaneous popular cultures and mass culture has encouraged, in addition to the globalized and unequal standardization of cultures, a process that leads to an increase in violence between different ethnicities, a phenomenon which is observed more and more frequently in late modern society. Based on this finding, it is believed that the development of strategies that facilitate intercultural communication could be a path that would lead different ethnicities to develop a more balanced cultural exchange. However, to develop an intercultural project that can embrace and disseminate the cultural diversity of different ethnicities, it is necessary to rescue spontaneous cultural narratives, to the detriment of the mass culture introduced by the use of the media.